Evaluation of the Acute Flaccid Paralysis Surveillance System of Polio Free in East Java, Indonesia, 2019 - Alya Hanifa Rasyidi1 , Anik Suroiyah2 , Laura Navika Yamani3 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Proving that the wild polio virus no longer exists in Indonesia, the symptoms must be found thatresemble polio. These symptoms are found in patients with AFP (Acute Flaccid Paralysis). AFP surveillanceis an observation made of all cases of acute paralysis or AFP in children aged <15 years who are vulnerableto polio. The priority problem that is still found in the East Java Provincial Health Office regarding AFPsurveillance is the reduction in the discovery of non-polio AFP cases and adequate specimens.Aims: The purpose of this study was to analyze the implementation of AFP surveillance activities in the EastJava Province Health Office in 2019.Methods: Data collection was carried out by primary and secondary to study the AFP surveillance overview.Primary data were obtained from in depth interviews with AFP surveillance program holders in East JavaProvincial Health Office. Secondary data is processed using Microsoft Office Excel, Epi Info and QuantumGIS.Results: The result is in 2019 the rate of non-polio AFP and the percentage of adequate specimens in EastJava Province has under the target. In 2019 there was a decrease compared to the previous year, the nonpolio AFP rate was 1.64 and the percentage of adequate specimens was 56.2%. Only as many as six districts/ cities in East Java Province had pass these two indicators.Conclusion: The lack of visits and reports from both the hospital and the community is one of causativefactor. Intensive and routine AFP surveillance is needed to monitor the emergence of polio cases